Desenvolvimento de plataforma biofotônica rápida e sustentável para detecção urinária da sepse neonatal de início tardio: estudo clínico de prova de conceito em recém-nascidos pré-termo de muito baixo peso - Lima, Caio Augusto de (2023)
Neonatal sepsis is a critical cause of morbidity and mortality affecting up to 2 cases per 1000 live births. There is a lack of diagnostic platforms for late-onset neonatal sepsis with reduced time to deliver results, which can provide suitable platforms for early diagnostics. The present study aimed to determine the discriminatory accuracy of a biophotonic Attenuated Total Reflection-Fourier Transform Infrared (ATR-FTIR) spectroscopy coupled with univariate analysis for late-onset neonatal sepsis and matched-control without sepsis in preterm-neonates. Here, an ultra-low volume of urinary samples from 45 samples, 6 late-onset sepsis in neonates, and 39 matched-control without sepsis in neonates were analyzed in a biophotonic coupled to univariate analysis associated with the receiver operating characteristic (ROC) curve. We demonstrated that three urinary vibrational modes of late-onset neonatal sepsis patients were distinct (p<0.05) from matched-control without sepsis. The vibrational modes 1337, 1152, and 1107 cm-1 were selected as potential infrared vibrational modes to discriminate late-onset neonatal sepsis. The vibrational mode at 1516 cm-1 presented a sensitivity of 100% and specificity of 92.31% also suggesting a potential use in infrared discriminatory analysis for late-onset neonatal sepsis. After validation with additional studies in higher cohorts, the vibrational modes at 1516, 1337, 1152 and 1107 cm-1 present potential to be applied in screening or diagnostic platforms for late-onset neonatal sepsis detection. The feasibility of execution in a biophotonic platform that delivers fast results from a 2 µl drop of urine indicates potential application as a proof-of-concept for late-onset neonatal sepsis detection.